Urinary excretion of high molecular weight adiponectin is an independent predictor of decline of renal function in type 2 diabetes - Kopf, Stefan; Oikonomou, Dimitrios; Eynatten, Maximilian von; Kieser, Meinhard; Zdunek, Dietmar; Hess, Gregor; Morcos, Michael; Forsblom, Carol; Bierhaus, Angelika; Groop, Per-Henrik; Nawroth, Peter Paul; Humpert, Per Magnus (Acta diabetologica, 2014)
Adiponectin and urinary adiponectin excretions have been ascribed a function in glomerular physiology and seem to indicate vascular disease in diabetes. The aim of this study was to compare the urinary excretion of albumin and adiponectin as predictors for decline of renal function in patients with type 2 diabetes and early kidney disease. Over 141 patients were screened for renal function (estimated GFR, ml/min*1.73 m2), albumin excretion rate (AER, mg/24 h), total as well as high molecular weight (HMW) urinary adiponectin excretion (ng/mol u-creatinine). AER and adiponectin excretion were studied as predictors of renal function after 1 year. After 1 year, 36 patients were in the upper quartile of eGFR decline and defined as progressors (delta eGFR = − 12.3 ± 6.3) while the remaining 105 patients were defined as non-progressors (delta eGFR = 1.4 ± 6.0). At baseline, HMW-adiponectin excretion was positively correlated with HbA1c (p < 0.001) and negatively with eGFR (p < 0.001), but not with AER (p = 0.14). Progressors showed increased urinary HMW-adiponectin at baseline (158[IQR41/479] vs. 65[24/168] ng/mol; p < 0.01), while total adiponectin (182[101/1534] vs. 345[118/1361] ng/mol) and AER (48[23/109] vs. 46[25/108] mg/24 h) excretion showed no differences between the groups. Multivariate logistic regression showed that HMW-adiponectin excretion was an independent predictor of renal progression in all patients (OR 1.86 [95 % CI 1.34-2.59]; p < 0.01), especially in those (n = 45) with normal AER at baseline (OR 2.16 [95 % CI 1.1-4.56]; p < 0.05). Urinary HMW-adiponectin but not AER improved the prediction of progressors in ROC analysis (AUC 0.72 [95 % CI 0.63-0.81] vs. 0.80 [95 % CI 0.71-0.90], p < 0.05). In conclusion, urinary HMW-adiponectin excretion may identify diabetes patients at increased risk for progression of kidney disease.
Published online: 24 December 2013
Gesehen am 25.03.2021
Gesehen am 10.11.2015